2015
DOI: 10.1590/1982-0224-20130219
|View full text |Cite
|
Sign up to set email alerts
|

Gross morphology of the brain of Pseudopimelodus bufonius (Valenciennes, 1840) (Siluriformes: Pseudopimelodidae)

Abstract: The gross morphology of the brain of the pseudopimelodid Pseudopimelodus bufonius is described and compared with congeners. Observations were made on removed brains after elimination of bones from the top of the skull and severing of the cranial nerves and the spinal cord. Nine morphometric characters associated with the major subdivisions of the brain were identified, seven of which revealed significant differences among the species examined. The corpus cerebelli in all examined species of the genus is the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…Abrahão & Shibatta () suggested that the corpus cerebelli is relatively large in all Pseudopimelodus Bleeker 1858 species when compared with species of Characiformes ( c.f . Pereira & Castro, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Abrahão & Shibatta () suggested that the corpus cerebelli is relatively large in all Pseudopimelodus Bleeker 1858 species when compared with species of Characiformes ( c.f . Pereira & Castro, ).…”
Section: Discussionmentioning
confidence: 97%
“…The brain of Spectracanthicus javae is similar to the brains of other siluriform species (Abrahão & Shibatta, ; Rosa, ; Angulo & Langeani, ). Pereira & Castro () described six putative synapomorphies for Siluriformes, all of them are present in the new species: the area postrema is almost as wide as long throughout its length; the rhombencephalon is well developed when compared to the size of the midbrain; the lobus vagi is developed; the lobus fascialis is present, although it is reduced in S. javae; the corpus cerebelli is horizontally developed; the tectum opticum is relatively smaller than the corpus cerebelli.…”
Section: Discussionmentioning
confidence: 99%
“…Datovo & Vari (), summarizing Wiley & Johnson (), revealed that within 180 major groups of Teleostei, 6% of synapomorphies are based on myology, 5% on splanchnology and 1% on neurology. Of the last, the first attempts to understand the neural‐complex date back to the beginning of the 20th century, but only from the mid‐1990s has neuroanatomy been used in systematic works on Antarctic fishes (Eastman & Lannoo, , , , , ) and more recently on Neotropical groups (Albert, ; Pupo, ; Abrahão & Shibatta, ; Pupo, ; Pereira & Castro, ). Likewise with other structures, such as the swimbladder capsule and Weberian apparatus, many studies were provided in the 19th century (Birindelli et al, ) and there has more recently been renewed interested in describing them (Birindelli et al, , ; Birindelli & Shibatta, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the Otophysi (composed by the Orders Cypriniformes, Characiformes, Siluriformes and Gymnotiformes), the study of the brain gross morphology has recently been addressed for gymnotiforms (Albert et al, 1998;Albert, 2001), in addition to the siluriforms Callichthyidae and Pseudopimelodidae (Abrahão & Shibatta, 2015), the Callichthyidae which was the subject of a Master's dissertation (Pupo, 2011) and the Characiformes studied in a Doctoral thesis (Pereira, 2014), both unpublished at this moment. These Otophysi brain studies have unequivocally shown that the central nervous system can be an important source of phylogenetically informative morphological characters, although relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%